Building Scientific Evidence to Support the Operationalization of the Global Biodiversity Framework - CGIAR Environmental Health and Biodiversity Impact Platform (CGIAR, 2024)
Webinar on ‘The Global Biodiversity Framework:Building scientific evidence to support the operationalization of the Kumnimng-Montreal Global Biodiversity Framework.'